Neosufisme sebagai Etika Pembangunan: Studi Atas Transformasi Spiritual Tarekat Qadiriyah Naqsyabandiyah Suryalaya di Era Orde Baru - Budi Rahman Hakim (Pusat Riset dan Inovasi Nasional, 2023)
This article discusses the transformation of the Qadiriyah Naqsyabandiyah (TQN) Suryalaya Order as a form of neo-Sufism that transformed into a development ethic in the New Order era. Under the charismatic leadership of Sheikh Ahmad Shohibul Wafa Tajul Arifin (Abah Anom), this order displays a dynamic face of Sufism, not only focusing on individual spirituality, but also actively responding to social and national issues. This study uses a literature study approach by critically examining various primary and secondary sources in the form of author dissertations, academic books, and reputable scientific journal articles. The main findings show that through collective rituals, character education, and ethical political positions, TQN Suryalaya acts as an agent of social and moral transformation. Abah Anom's inclusive leadership model and participatory spiritual practices make this order relevant in the context of modern development. This study emphasizes the importance of the order as an agent of spiritual and social development in facing ethical crises, modern disorientation, and post-reform national challenges.